2011
DOI: 10.1073/pnas.1104261108
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia triggers a proangiogenic pathway involving cancer cell microvesicles and PAR-2–mediated heparin-binding EGF signaling in endothelial cells

Abstract: Highly malignant tumors, such as glioblastomas, are characterized by hypoxia, endothelial cell (EC) hyperplasia, and hypercoagulation. However, how these phenomena of the tumor microenvironment may be linked at the molecular level during tumor development remains ill-defined. Here, we provide evidence that hypoxia up-regulates protease-activated receptor 2 (PAR-2), i.e., a G-protein–coupled receptor of coagulation-dependent signaling, in ECs. Hypoxic induction of PAR-2 was found to elicit an angiogenic EC phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(223 citation statements)
references
References 35 publications
6
211
1
3
Order By: Relevance
“…In addition to TF, hypoxic stress has been shown to modulate PAR1 expression in tumor cell lines (32,33). Furthermore, our recent study observed increased PAR1 and PAR2 staining around necrotic areas in samples from patients with GBM (22).…”
Section: Hypoxic Induction Of Par Expression In P7 and St1 Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to TF, hypoxic stress has been shown to modulate PAR1 expression in tumor cell lines (32,33). Furthermore, our recent study observed increased PAR1 and PAR2 staining around necrotic areas in samples from patients with GBM (22).…”
Section: Hypoxic Induction Of Par Expression In P7 and St1 Cellsmentioning
confidence: 95%
“…No significant FXa generation was observed in the absence of FVIIa. Hypoxia has been shown to markedly increase TF-containing extracellular vesicle secretion in glioma cells (32). Therefore, the present study investigated whether hypoxia increases the secretion of MVs into the conditioned media of P7 and ST1 cell cultures.…”
Section: Shedding Of Procoagulant Mvs By P7 and St1 Cells Tf Has Beenmentioning
confidence: 99%
“…Glioblastoma cells grown under hypoxic conditions were shown to produce exosomes that deliver pro-angiogenic factors such as IL8 and PDGF to ECs (121). An additional example is the transfer of tissue factor by tumor-cell derived exosomes to ECs, resulting in activation of GPCR proteaseactivated receptor 2 and subsequent upregulation of HB-EGF, promoting an angiogenic EC phenotype (122). Promotion of brain metastasis by breast cancer cell-derived exosomal miRs after transfer to ECs was documented in two reports (115,123).…”
Section: Metastasis-related Interactions Between Cancer Cell-derived mentioning
confidence: 99%
“…Hypoxia has been reported to induce increased release of proangiogenic extracellular vesicles (6,(39)(40)(41). Hypoxia-induced…”
mentioning
confidence: 99%